Reducing the waiting time before receiving cystoscopy with changing ureteral stent operation of outpatient - Onmasen, Nattapol; Krongtham, Patcharin; Janchay, Arisa; Thongmoonchai, Siraprapa; Poorahong, Wanatsanan; Thanakumcheep, Piyapach (Thammasat University Hospital Journal Online, 2022)
Introduction: The percentage of 96.55 of outpatients who needed cystoscopy with changing ureteral stents had to wait more than 30 minutes before the procedure. Patients had an average waiting time of 2 hours 33 minutes and 22 seconds. The reason for the patient’s appointment falls within the same time frame. It does not segregate according to the difficulty of surgery. The service process is different. It affects patients both physically and mentally. Personnel have an increased workload. The service does not meet the agency’s goals and the hospital’s strategy. Therefore, we focus on developing nursing service systems using LEAN and digital transformation concepts to be a qualitative and sustainable organization. Objective: To reduce the waiting time before receiving cystoscopy with changing ureteral stent operation for outpatients who have a waiting time of more than 30 minutes. That’s a decline from 96.55 percent to less than 19.31 percent (a decrease of 80 percent) within 8 months. Methods: 1) Improve patient appointment and outpatient surgical scheduling systems. 2) Pre-visit telephone nursing according to guidelines. 3) Provide patient services according to guidelines. 4) Develop an appointment system into the Hospital Information System. Results: The percentage of waiting time of more than 30 minutes before the procedure in outpatient who needed cystoscopy with changing ureteral stent decreased from 96.55 percent to 50 percent (a decrease of 46.55 percent). Conclusion: Reducing the waiting time before the outpatient’s appointment with cystoscopy with changing ureteral stent achieved to a duration of less than 30 minutes.The methods are improving the outpatient appointment system to have a clear period of time, separating the difficulty of surgery and pre-visit telephone nursing to advise patients before receiving procedure according to the guidelines.Personnel serve patients according to procedures in the same way. We bring problems and outcomes to improve appointments into the Hospital Information System. This resulted in an outpatient who needed cystoscopy with changing ureteral stent having a waiting time of more than 30 minutes, a decrease of 46.55%.